Threats to Autonomy from Emerging ICTs - Dainow, Brandt (Australasian Journal of Information Systems, 2017)
This paper examines threats to autonomy created by significant emerging ICTs. Emerging ICTs cover a wide range of technologies, from intelligent environments to neuroelectronics, and human autonomy is potentially threatened by all of them in some way. However, there is no single agreed definition of autonomy. This paper therefore considers the ways in which different accounts of autonomy are impacted by the different IC technologies. From this range of threats we will derive some properties which any ICT must exhibit in order to threaten human autonomy. Finally, we will show how the range of definitions of autonomy creates problems for customary approaches to vale-sensitive design, and how this indicates a need for greater flexibility when attempting to improve the ethical status of emerging ICTs.